THE BASICS OF THE TRAINING METHOD IN WRESTLING SPORT - Jumaniyazov, Q.T.; Utepbergenova, A. (SCIENCE and SOCIETY, 2023)
This article describes the principles of modern pedagogical training of wrestlers, teacher activity. Also, the duties of the teacher to implement the principle of demonstration in sports wrestling are indicated.
Keywords: wrestling sport; coach; principle; consciousness; refereeing; educational training